Harnessing antibody-mediated recognition of the intracellular proteome with T cell receptor-like specificity - Haus-Cohen, Maya; Reiter, Yoram (Frontiers in Immunology, 2024)
The clinical success of cancer immunotherapy has driven ongoing efforts to identify novel targets that can effectively guide potent effector functions to eliminate malignant cells. Traditionally, immunotherapies have focused on surface antigens; however, these represent only a small fraction of the cancer proteome, limiting their therapeutic potential. In contrast, the majority of proteins within the human proteome are intracellular, yet they are represented on the cell surface as short peptides presented by MHC class I molecules. These peptide-MHC complexes offer a vast and largely untapped resource for cancer immunotherapy targets. The intracellular proteome, including neo-antigens, presents an exciting opportunity for the development of novel cell-based and soluble immunotherapies. Targeting these intracellular-derived peptide-MHC molecules on malignant cell surfaces can be achieved using specific T-cell receptors (TCRs) or TCR-mimicking antibodies, known as TCR-like (TCRL) antibodies. Current therapeutic strategies under investigation include adoptive cell transfer of TCR-engineered or TCRL-T cells and CAR-T cells that target peptide-MHC complexes, as well as soluble TCR- and TCRL-based agents like bispecific T cell engagers. Recent clinical developments in targeting the intracellular proteome using TCRL- and TCR-based molecules have shown promising results, with two therapies recently receiving FDA approval for the treatment of unresectable or metastatic uveal melanoma and synovial sarcoma. This review focuses on the processes for selecting and isolating TCR- and TCRL-based targeting moieties, with an emphasis on pre-clinical and clinical studies that explore the potential of peptide-MHC targeting agents in cancer immunotherapy.